Hidrolisis Pati Garut Secara Enzimatis untuk Pembentukan Siklodekstrin - Erliza Noor (Jurnal Ilmu Pertanian Indonesia, 2008)
Modified starch has important role in chemical, cosmetic, pharmaceutical, and food industries. Cyclodextrin was prepared based on garut starch using starch hidroying enzime namely 0-amylase, 0-amylase, pullulanase and glukoamylase. Cyclication to form cyclodextrin was obtained using CGTase. The highest concentration of cyclodextrin was obtained by glucoamylase and CGTase concentration of 150 unit/g substrate which was 81.11g.l-1  in 90 minutes. Keywords: 0-amylase, 0-amylase, cyclodextrin, CGT-ase, gantt starch, glukoamylase, pullulanase